Collective action, political regimes and economic growth: towards a theoretical discussion - Zegarra B., Luis Felipe (2000)
Not a few people believe that the lack of debate and negotiation is in favor of the economic growth, because it permits the application of economic measures without taking into account the interests of certain pressure groups. In this paper, we try to demonstrate that the reality is totally contrary. For that, we discuss theoretically how the production of the rules of the game is affected by the characteristics of the political market, particularly by the collective action and by the nature of the political regime. On the basis of this analysis, we conclude that the rules of the game are in favor of the economic growth if the transaction costs to conform a group are depreciable, if the groups congregate wide sectors of the society and have adequate accountability mechanisms, and if the political power is not concentrated.